2016
DOI: 10.1007/s00380-016-0837-7
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the percentage of cholesterol efflux capacity and total cholesterol efflux capacity in patients with or without coronary artery disease

Abstract: We hypothesized that cholesterol efflux capacity is more useful than the lipid profile as a marker of the presence and the severity of coronary artery disease (CAD). Therefore, we investigated the associations between the presence and the severity of CAD and both the percentage of cholesterol efflux capacity and total cholesterol efflux capacity and the lipid profile including the high-density lipoprotein cholesterol (HDL-C) level in patients who underwent coronary computed tomography angiography (CTA). The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…Thus, we should consider not only the level of HDL-C but also HDL functionality. We previously reported that the calculated total cholesterol efflux capacity that depended on the HDL-C level was significantly correlated with the presence of CAD at the time of CCTA [23].…”
Section: Discussionmentioning
confidence: 97%
“…Thus, we should consider not only the level of HDL-C but also HDL functionality. We previously reported that the calculated total cholesterol efflux capacity that depended on the HDL-C level was significantly correlated with the presence of CAD at the time of CCTA [23].…”
Section: Discussionmentioning
confidence: 97%
“…After excluding 166 other studies designed as case reports, letters to editor, review articles, in vitro studies, animal studies, 41 articles in full-text article were assessed for eligibility. Finally, 18 articles reporting outcomes of interest were included in the meta-analysis [2,3,7,8,10,[13][14][15][16][17][18][19][20][21][22][23][24][25]. Of them, 12 studies were designed as case-control studies and 6 were cohort studies.…”
Section: Study Selection and Characteristics Of The Included Studiesmentioning
confidence: 99%
“…Eight of them analyzed the association between CEC and the risk of stable CAD or ACS [7,8,16,18,19,[21][22][23]. Four studies reported the prognosis of stable CAD or ACS [2,10,17,25].…”
Section: Study Selection and Characteristics Of The Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The cholesterol efflux capacity (CEC) of HDL is modified in CVD [ 22 26 ] , metabolic syndrome [ 27 ] , and during acute inflammation [ 28 ] . How distinct CEC and HDL-C are as biomarkers of disease has been debated, with some studies observing reduced CEC independent of changes in HDL-C [ 22 - 23 , 25 , 28 30 ] , while others find that CEC and HDL-C changes correlate [ 24 , 26 - 27 ] . Possible mechanisms to explain diminished CEC in most of these studies is increased HDL-associated serum amyloid A (SAA) [ 28 ] and reduced HDL-associated paraoxonase 1 (PON-1) [ 26 ] in inflammatory states, which will be discussed below.…”
Section: Changes In Hdl Cholesterol Efflux Capacitymentioning
confidence: 99%